SISTEM PAKAR BERBASIS WEB UNTUK MENGETAHUI KEKURANGAN VITAMIN PADA MANUSIA WEB BASED EXPERT SYSTEM TO DETERMINE THE VITAMIN DEFICIENCY IN HUMANS (Information Technology and Telematics, 2015)
Abstract Fruit is a source of vitamins and various types of vitamin exist in the fruit. Fruits have many useful properties for the benefit of humans, therefore, fruits contain vitamins called the warehouse needed to be consumed by manusia.Tidak only fruits have vitamins that are beneficial to the body, but still many in the community who have not forgotten of the vitamins contained in fruit. Not all of the problems that occur in agriculture buahdapat practical handled by petanibuah. It takes special knowledge of an expert in handling it. But often when these problems occur, experts are not always available. In this case an expert system to help make computing as a solution without the presence of a human expert. The purpose of this research is to create a web-based expert system to determine the vitamin deficiency in humans online. This system designing expert system that can help the ordinary people who are not informed about the benefits and vitamin deficiency in humans to be authors carefully. Making the system using the programming language PHP and MySQL, the methods used in the development of this system is the method of prototyping (Collecting Supplies, Building Prototyping, Evaluation prototyping, Encoding System, System Testing, Evaluation System, Using System). Results of consultations with using this application provides the same results of consultations if done manually. Keywords: Expert System, vitamin deficiency, Php, MySQL